2015
DOI: 10.1590/0100-2945-222/14
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Fenológica Das Diferentes Estruturas De Frutificação Das Macieiras 'Gala' E 'Fuji' Na Região De Caçador-Sc

Abstract: PHenologicAl evAluAtion of different fruiting HAbits of 'gAlA' And 'fuJi' APPles in tHe soutHern brAZilAbstrAct -Apple shows two distinct phases that characterizes its annual cycle: dormancy and vegetative/ reproductive growth. The importance of knowing the influence of climate conditions on tree reproductive processes and furthermore, developing technologies that minimize the future effects increases upon the global warming predictions becomes concerning. The goal of this study was to characterize the behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Petri et al [7] observed that bud break promoters mixed with MO advanced apple tree flowering. There were small variations in the number of days from the beginning to the end of flowering between the years studied and these differences found in the beginning of sprouting and flowering depended on the climatic conditions of the year, and the variation in the number of cold units that occurs in winter, influences the flowering period [16]. However, the control treatment always had a longer flowering period.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Petri et al [7] observed that bud break promoters mixed with MO advanced apple tree flowering. There were small variations in the number of days from the beginning to the end of flowering between the years studied and these differences found in the beginning of sprouting and flowering depended on the climatic conditions of the year, and the variation in the number of cold units that occurs in winter, influences the flowering period [16]. However, the control treatment always had a longer flowering period.…”
Section: Resultsmentioning
confidence: 82%
“…Usually the terminal buds, as they are floriferous, sprout more than the axillary buds, due to t requirement and apical dominance [19]. According to Francescatto et al [16], the lack of axillary bud break favors the terminal bud break and compromises the formation of reproductive organs, favoring excessive vegetative development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In floral induction, hormonal exchanges occur that define whether the bud remains vegetative or become a flower bud for the next cycle, all commanded by genes. In apple trees, this process usually occurs 6 to 8 weeks after full bloom, but in subtropical climate conditions, it can continue until post-harvest, mainly in axillary buds, although the greatest intensity is in this period [2]. Also, several factors can influence floral induction, such as plant management and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…The floral differentiation is often associated with the stoppage of the growth of the shoot buds. In mild winter conditions and where there is no water deficit, in general, spur buds stop growth two to four weeks after flowering, while long shoot buds depend on plant and environmental conditions and often extend to post-harvest [2]. Considering the vegetative growth antagonistic to the formation of flower buds, however, it does not necessarily occur in all cultivars.…”
Section: Introductionmentioning
confidence: 99%